2020
DOI: 10.3390/w12020407
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light Intensity and Exposure Period on the Growth and Stress Responses of Two Cyanobacteria Species: Pseudanabaena galeata and Microcystis aeruginosa

Abstract: Light is an important factor that affects cyanobacterial growth and changes in light can influence their growth and physiology. However, an information gap exists regarding light-induced oxidative stress and the species-specific behavior of cyanobacteria under various light levels. This study was conducted to evaluate the comparative effects of different light intensities on the growth and stress responses of two cyanobacteria species, Pseudanabaena galeata (strain NIES 512) and Microcystis aeruginosa (strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Our previous study on the effects of 8 days of exposure to non-varying, high-light intensities (300 µmol•m −2 •s −1 and 600 µmol•m −2 •s −1 ) confirmed that the OD 730 and chlorophyll-a contents of cyanobacteria (Pseudanabaena galeata and M. aeruginosa) were significantly reduced, which was associated with oxidative stress [60]. Although the present research confirmed the relationships between varying oxidative stress and antioxidant responses with light intensity, further investigation into the longer-term effects on the growth and pigmentation of cyanobacteria is warranted.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Our previous study on the effects of 8 days of exposure to non-varying, high-light intensities (300 µmol•m −2 •s −1 and 600 µmol•m −2 •s −1 ) confirmed that the OD 730 and chlorophyll-a contents of cyanobacteria (Pseudanabaena galeata and M. aeruginosa) were significantly reduced, which was associated with oxidative stress [60]. Although the present research confirmed the relationships between varying oxidative stress and antioxidant responses with light intensity, further investigation into the longer-term effects on the growth and pigmentation of cyanobacteria is warranted.…”
Section: Discussionmentioning
confidence: 59%
“…The difference in antioxidant levels of the two species can be related to their behavioral characteristics. The M. aeruginosa is a buoyant species that floats in a range of depths and might have higher tolerance to oxidative stress [60,61] than benthic P. ambiguum. However, in the present study, both species experienced same light intensity variance as the cultures were mixed periodically.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [10] provided an improved modeling approach on the role of turbulence mixing on the growth of Microcystis aeruginosa as a means of affecting differential nutrient transfer between this cyanobacterium and Scenedesmus quadricauda, frequently occurring chlorophyte in eutrophic freshwaters. Another autoecological approach is given by Muhetaer et al [17]. In this study, the authors conducted experiments in order to evaluate the comparative effects of different light intensities on the growth and stress responses of two bloom-forming cyanobacterial species, Pseudanabaena galeata (strain NIES 512) and Microcystis aeruginosa (strain NIES 111) for a few days.…”
Section: Contributionsmentioning
confidence: 99%
“…In this direction, a deeper understanding of the mechanisms that determine cyanobacterial bloom structure and toxin production become a target for managing practices [5,6]. This Special Issue, entitled "Advancing Knowledge on Cyanobacterial Blooms in Freshwaters", includes 11 research papers [9][10][11][12][13][14][15][16][17][18][19] and aims to bring together the recent research of multiand interdisciplinary approaches from the field to the laboratory and back again, driven by working hypotheses based on any aspect from ecological theory to applied research on mitigating cyanobacterial blooms.…”
Section: Introductionmentioning
confidence: 99%
“…Cyanobacteria blooms have several detrimental effects on the limnological ecosystem, local economy, and human health. Cyanobacteria blooms limit light, which inhibits the growth of macrophytes [9]; they cause anoxia after death and mineralization, which disrupts fisheries and results in fish kills [10]; they decrease property values around the affected lake [11]. Many cyanobacteria species produce intra-and extracellular toxins [12,13], and cyanobacteria blooms or their toxins have been associated with many human health disorders [14,15].…”
Section: Introductionmentioning
confidence: 99%